Reinforced Feedback in Virtual Environment for Plantar Flexor Poststroke Spasticity Reduction and Gait Function Improvement - Luque-Moreno, Carlos (Biomed Res Int, 2019)
BACKGROUND: Ankle spasticity is a frequent phenomenon that limits functionality in poststroke patients. OBJECTIVES: Our aim was to determine if there was decreased spasticity in the ankle plantar flex (PF) muscles in the plegic lower extremity (LE) and improvement of gait function in stroke patients after traditional rehabilitation (TR) in combination with virtual reality with reinforced feedback, which is termed “reinforced feedback virtual environment” (RFVE). METHODS: The evaluation, before and after treatment, of 10 hemiparetic patients was performed using the Modified Ashworth Scale (MAS), Functional Ambulatory Category (FAC), and Functional Independence Measure (FIM). The intervention consisted of 1 hour/day of TR plus 1 hour/day of RFVE (5 days/week for 3 weeks; 15 sessions in total). RESULTS: The MAS and FAC reached statistical significance (P < 0.05). The changes in the FIM did not reach statistical significance (P=0.066). The analysis between the ischemic and haemorrhagic patients showed significant differences in favour of the haemorrhagic group in the FIM scale. A significant correlation between the FAC and the months after the stroke was established (P=−0.711). Indeed, patients who most increased their score on the FAC at the end of treatment were those who started the treatment earliest after stroke. CONCLUSIONS: The combined treatment of TR and RFVE showed encouraging results regarding the reduction of spasticity and improvement of gait function. An early commencement of the treatment seems to be ideal, and future research should increase the sample size and assessment tools.